Promoting economic empowerment through effective implementation and linking social capital in urban agriculture programs - Nazuri, Nur Shuhamin; Rosnon, Mohd Roslan; Salim, Sara Shakilla Mohd; Ahmad, Mohamad Firdaus; Suhaimi, Siti Shazwani Ahmad; Safwan, Nur Syazwani Zulaikha (South Florida Publishing, 2023)
Objective: Urban agriculture (UA) is seen as a way to tackle food insecurity in cities and boost economic growth. Yet, achieving economic empowerment through UA programs is challenging. This research aims to identify the values linked to community participation in UA in the Klang Valley area of Malaysia and understand how these values contribute to economic empowerment with the help of social connections. Methods: Data was collected from 180 respondents who participated in UA programs, using multistage random sampling. Partial Least Square Structural Equation Modeling (PLS-SEM) was applied to analyze the relationships between various variables. Mediating effect analysis was conducted to explore the theoretical indirect relationships between constructs.Results and conclusion: The results indicate that two dimensions, planning and implementation, contribute significantly to linking. This study also highlighted that implementation linking have positive effects on economic empowerment meanwhile planning negatively affects economic empowerment. By fostering networks and relationships between these groups, social capital linking facilitates the identification and mobilization of resources and support for UA initiatives.Research implications: Striking a balance between planning and other participation elements is crucial for program success. Additionally, the study reveals that linking social capital plays a significant role in enhancing the positive outcomes of program implementation on economic empowerment. Building strong social connections and collaborations within the community are essential for promoting economic empowerment effectively.